Astaxanthin Induces the Expression of CatSper1 Gene and Protects Sperms in Toxicity Induced by Cadmium in Mice - Saberi, Ensieh; Mohammadrezaei, Fereshteh Mir; Jazayeri, Omid; Fathi, Nazanin; Moghadam, Akbar Hajizadeh (Drug Research, 2021)
Cadmium (Cd) as a heavy metal damages testis and decreases fertility, however, antioxidants can improve sperm parameters and decrease male infertility. In this study we investigated the effect of astaxanthin (AST) on sperm parameters, expression levels of CatSper1 and CatSper2 genes in presence of Cd in mice. Thirty adults’ mice were divided into 4 groups, sham group received olive oil and saline (olive oil is the solvent of AST and saline is the solvent of Cd), Cd group received 1 mg/kg Cdcl2, a group received 10 mg/kg AST and 1 mg/kg Cdcl2 and a group received 10 mg/kg AST. The treatments were done intraperitoneally for 14 days. After 14 days sperm parameters were analyzed. Malondialdehyde level, catalase enzyme activity, the alteration of CatSper1 and CatSper2 genes expression were measured in testis. Results showed that Sperm count, viability, CatSper1 gene expression and catalase activity significantly decreased by Cd compared to sham group. Cd significantly increased sperm DNA fragmentation (SDF), abnormal sperm morphology and malondialdehyd level compared to sham group. AST significantly increased sperm count, viability and CatSper1 gene expression and decreased SDF and abnormal sperm in comparison with Cd group. AST protected testis and decreased oxidative stress induced by Cd. Our findings indicated that AST could protect sperm DNA, enhanced CatSper1 gene expression and sperm quality in presence of Cd. No significant differences were found in CatSper2 expression among treatments. Therefore, AST as a strong antioxidant can help to protect the potential of fertility against Cd toxicity.
Keywords: Astaxanthin; Cadmium; Sperm DNA fragmentation; testis; CatSper1